Translation as a Writing Strategy and the Resulting Negative Language Transfer - Stanojević Gocić, Maja P.; Jankovic, Anita V. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Translation is a common learning stratagy used in beginner levels of learning English. The inefficacy of the strategy is most prominent when employed in writing. Therefore, the aim of the paper is emphasize the benefits of incorporating the learning strategies into the teaching process. In addition, implementing contrastive ananlysis in teaching would boost students’ understanding of the differences between Serbian and English, which are often overlooked—thus resulting in negative language transfer. It is important to underline that translation is not a uniform word-by-word process, but the transfer of meaning from one language to another, taking into account the differences between the language systems and cultures. This paper presents the results of the error analysis resulted from the inefficient application of translation as a writing strategy. The study was conducted on the sample of 35 beginner English students of the College of Applied Professional Studies in Vranje.